Novel photodynamic therapy using two-dimensional NiPS3 nanosheets that target hypoxic microenvironments for precise cancer treatment - Wu Zongze; Liu Quan; Wageh Swelm; Sun Zhe; Al-Hartomy Omar A.; Al-Sehemi Abdullah G.; Yan Lesen; Chen Jiaojuan; Zhang Wenjian; Yang Jilin; Zhang Han; Liu Liping (Nanophotonics)
Photodynamic therapy (PDT) is a highly promising modality against cancer, but its efficacy is severely limited by the low oxygen content in solid tumors. In this study, a smart photosensitive NiPS3 nanosheet was developed to solve the problem of low oxygen to allow PDT to be performed against tumors. The photosensitized ROS generation mechanism of NiPS3 is the photon-generated electron-hole pathway, which can generate O2 ·− and ·OH at the conduction band and valance band, respectively. More crucial is that ·OH generation doesn’t need O2, and the O2 ·− can also work in a low O2 environment, and depleting oxygen in tumor cells. Modified with triphenylphosphine (TPP) and based on density functional theory (DFT) calculations and experimental data, the NiPS3@TPP nano-system underwent targeted action toward mitochondria. In vitro experiments demonstrated that the reactive oxygen species (ROS) produced by NiPS3@TPP altered mitochondrial membrane permeability, which not only prolonged the PDT effect but also resulted in mitochondria apoptosis pathways inducing an apoptosis cascade. In vivo experiments demonstrated the targeting capability with low toxicity of the NiPS3@TPP nano-system. Tumor targeting at the tested dose indicated that it represented a promising biocompatible photosensitizer for in vivo biomedical applications.